The role of PDIA3 in oral squamous cell carcinoma and its value as A diagnostic and prognostic biomarker - Lin Wang; Xinxin Wang; Jia Zhang; Jiafeng Duan; Chengfang Tang; Linmei Zhang; Hui Zeng; Hantong Li; Yuefan Li; Yan Zhou (Heliyon, 2023)
Background: This study aimed to investigate the role of protein disulfide isomerase A3 (PDIA3) in oral squamous cell carcinoma (OSCC) and evaluate its significance as a diagnostic and prognostic biomarker. Methods: Comprehensive bioinformatics analysis of the OSCC dataset from The Cancer Genome Atlas (TCGA) was performed. PDIA3 was depleted in CAL27 and SCC25 OSCC cells by transfection with PDIA3-specific siRNA oligos. The effects of PDIA3 downregulation on cell viability, apoptosis, and cell migration were evaluated using CCK8, ELISA, and wound healing assays, respectively. Results: The mRNA and protein expression of PDIA3 was significantly up-regulated in OSCC tissues compared to adjacent normal tissues. Knockdown of PDIA3 led to significantly decreased cell viability, increased apoptosis, and suppressed migratory ability in OSCC cells. The Kaplan-Meier survival curve showed that patients with higher PDIA3 expression levels had shorter survival than those with low PDIA3 levels. The receiver operating characteristic (ROC) curve indicated that PDIA3 had high sensitivity and accuracy for detecting OSCC (area under the curve (AUC): 0.917, CI: 0.879–0.955). Univariate and multivariate Cox regression analyses identified PDIA3 as an independent prognostic factor of OSCC. Furthermore, the depletion of PDIA3 inhibited AKT activity in OSCC cells. Gene set enrichment analysis (GSEA) indicated that PDIA3 is involved in various important biological functions and signaling pathways closely related to cancer development. Conclusion: PDIA3 plays an oncogenic role in OSCC and represents a good candidate as a diagnostic and prognostic biomarker for OSCC.